New simple and efficient method of DNA isolation from pear leaves rich in polyphenolic compounds - Bokszczanin, K.; Przybyla, A. A. (International Journal of Horticultural Science, 2006)
This study aimed to establish a new protocol for DNA isolation from the Pyrus genus to get high quality DNA that is suitable for the generation of molecular markers, such as RAPD and AFLP. This method is based on modified CTAB extraction procedure (Aldrich & Cullis, 1993). For isolation of high-quality DNA we used copper (II) acetate treatment that enabled fixation and removing of tannins, present in abundance in Pyrus. DNA yield from this procedure is high. DNA is completely digestible with restriction endonucleases and amplifiable in the PCR, indicating freedom from common contaminating polyphenolic compounds.